BRCA2 controls DNA:RNA hybrid level at DSBs by mediating RNase H2 recruitment - Giuseppina D’Alessandro (Nature Portfolio, 2018)
Long non-coding RNAs transcribed at DNA damaged sites can play part in DNA damage response. Here the authors reveal that damaged induced lncRNAs can form DNA:RNA hybrids at resected DNA-ends. These hybrids are involved in recruiting HR-mediated repair machinery which, in turn, controls their level at DSBs.